Mechanisms of Sucrose and Non-Nutritive Sucking in Procedural Pain Management in Infants - Sharyn Gibbins; Bonnie Stevens (Pain Research and Management)
The administration of sucrose with and without non-nutritive sucking (NNS) has been examined for relieving procedural pain in newborn infants. The calming and pain-relieving effects of sucrose are thought to be mediated by endogenous opioid pathways activated by sweet taste. The orogustatory effects of sucrose have been demonstrated in animal newborns, and in preterm and full term human infants during painful procedures. In contrast to sucrose, the analgesic effects of NNS are hypothesized to be activated through nonopioid pathways by stimulation of orotactile and mechanoreceptor mechanisms. Although there is uncertainty as to whether the effects of sucrose and NNS are synergistic or additive, there is sufficient evidence to support the efficacy of combining the two interventions for procedural pain relief in infants. In this review article, the underlying mechanisms of sucrose and NNS, separately and in combination for relieving procedural pain in preterm and full term infants, are examined. Clinical and research implications are addressed.